Distorsiones cognitivas y su repercusión en la autoestima de un adulto en rehabilitación fundación COTEMAC CETAC – Quevedo - Contreras Jurado, Shiley Adali (2021)
The present case study aims to determine how cognitive distortions affect the self-esteem of an adult in Rehabilitation, foundation Cotemac Cetac - Quevedo, which used a non-experimental research, correlational and descriptive research, which has led to obtaining a statistical analysis and develop the variables of the topic. The instruments used are the following: IPA (Automatic Thought Inventory), TDC Test, with the use of techniques and instruments performed it was possible to collect detailed information resulting in Cognitive Distortions Reward Fallacy (55 %), Divine guilt (20%), You should (15), Fallacy of control (10%) and in terms of self-esteem, a low self-esteem is estimated in the adult who is in Rehabilitation, in addition with these results it was possible to elaborate a psychotherapeutic plan focused on cognitive behavior that will help the patient to improve their quality of life in their environment and thus ensure that they shape their mentality and habits for life.